Address Broadcast over Station CFCF, Montreal, February 18, 1948 - McCloy, John J. (World Bank, Washington, DC, 2019)
John J. McCloy, President of the International Bank for Reconstruction and Development, commented on the interdependence of Canada with the world economy. He discussed the sources of capital the Bank draws upon for lending and guarantees. He noted that the European Recovery Program (Marshall Plan) does not conflict with role of the International Bank. He discussed the economic situation of Latin America and its relation to Europe. He warned that the European Recovery Program has limitations.